Torsional angle dependence and switching of inner sphere reorganisation energies for electron and hole transfer processes involving phenyl substituted diketopyrrolopyrroles; a density functional study. (February 2015) - Calvo-Castro, Jesus; McHugh, Callum J.; McLean, Andrew J.
Abstract: Determination of inner sphere reorganisation energies is important in the development of organic charge mediating materials and electron transfer reactions. In this study, hole and electron inner sphere reorganisation energies, λ h and λ e respectively, have been computed for the first time for a series of structurally related diketopyrrolopyrrole (DPP) molecular motifs. Inner sphere reorganisation energies for self-exchange electron transfer reactions are calculated as being lower than those associated hole transfer processes in model planar phenyl and thiophenyl substituted DPP systems. It is found that λ e  < λh for all planar ring/DPP core structures examined. The effect on λ h/e of non-planarity between phenyl substituents and DPP core is explored in detail. The relative ordering of λ h and λe is dependent upon the torsional angle of phenyl rings and reverses at twist angles of greater than 60° such that λ e  >  λ h . Graphical abstract: Inner sphere reorganisation energies for self-exchange electron transfer ( λ e ) reactions are calculated as being lower than those associated hole transfer processes ( λ h ) in model planar phenyl and thiophenyl substituted DPP systems. It is found that λ e  <  λ h for all planar ring/DPP core structures examined. The effect on λ h/e of non-planarity between phenyl substituents and DPP core is explored in detail. The relative ordering of λ h and λ e is dependent upon the torsional angle of phenyl rings and reverses at twist angles of greater than 60° such that λ e  >  λ h . Highlights: Inner sphere reorganisation energies determined for commonly employed DPP systems. λ e  <  λ h for both phenyl and thiophenyl substituted DPPs. λ e sensitive to torsional constraint: λ e  >  λ h at high phenyl torsion angles (>60°). λ h less sensitive and largely independent of phenyl versus thiophenyl substitution.